2020
DOI: 10.4067/s0717-75182020000100080
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between food consumption of pregnant women and birth weight of newborns

Abstract: The aim of this study was to investigate the relationship between food consumption of 99 pregnant women aged 16-44 years who gave birth at a maternity hospital in Rio de Janeiro and newborn birth weight. Maternal consumption of unprocessed or minimally processed and ultra-processed foods was evaluated through the Food Consumption Markers Form. For ultra-processed foods, most pregnant women regularly consumed sweets (73.7%), soft drinks (71.7%), sausages (65.7%), salted crackers (63.6%) and fried foods (55.6%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…After the removal of duplicates, 4.918 article titles and abstracts were screened. Of these, 151 full-text articles were further assessed for eligibility and, finally, 61 studies [ 4 , 18 , 19 , 20 , 21 , 22 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the removal of duplicates, 4.918 article titles and abstracts were screened. Of these, 151 full-text articles were further assessed for eligibility and, finally, 61 studies [ 4 , 18 , 19 , 20 , 21 , 22 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted in Africa [ 50 , 51 ], Asia [ 19 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], America [ 4 , 18 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 89 ], Europe [ 20 , 21 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , …”
Section: Resultsmentioning
confidence: 99%
“…The detailed characteristics of the 42 included studies are shown in Table 1 . There were 23 cohort studies ( 19 21 , 26 , 27 , 31 , 32 , 36 , 39 , 40 , 42 45 , 49 52 , 55 , 57 , 58 , 61 , 62 ), 10 cross-sectional studies ( 24 , 28 , 33 , 34 , 37 , 47 , 48 , 53 , 56 , 59 ), seven case-control studies ( 25 , 29 , 35 , 41 , 46 , 54 , 60 ), and two interventional studies ( 30 , 38 ). There were 13 studies rated as Good ( 19 , 21 , 26 , 30 32 , 36 , 45 , 49 , 50 , 52 , 58 , 61 ), 27 as Fair ( 20 , 24 , 25 , 27 29 , 33 35 , 39 44 , 46 – 48 , 51 , 53 57 , 59 , 60 , 62 ), and two as Poor ( 37 ,…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the quality assessment is presented in Supplementary Material 3 . There were over 20 types of birth outcomes, including birth weight (BW) ( 19 21 , 24 , 26 28 , 30 34 , 36 , 38 , 39 , 43 , 45 , 47 , 48 , 50 , 62 ), birth length (BL) ( 19 , 21 , 26 , 30 32 , 34 , 36 , 38 , 45 , 48 ), head circumference ( 19 , 21 , 26 , 30 32 , 39 , 45 , 48 ), low birth weight (LBW) ( 28 , 37 , 38 , 40 , 49 , 53 , 55 , 59 , 61 ), PB ( 19 , 27 , 28 , 40 , 49 , 52 , 57 , 61 ), small for gestational age (SGA) ( 19 , 29 , 31 , 44 , 54 , 57 , 58 , 61 ), large for gestational age (LGA) ( 19 , 31 , 57 , 58 , 61 ), mid-upper arm circumference ( 26 , 32 ...…”
Section: Resultsmentioning
confidence: 99%
“…Rodrigues et al(41) encontraron, en madres atendidas en Río de Janeiro, Brasil, que el consumo de alimentos ultraprocesados, como dulces y embutidos, se asoció con bajo peso al nacer en el recién nacido. En contraste, Rohatgi et al(42), en población estadounidense, reportaron que el consumo de alimentos ultraprocesados conlleva un incremento en el porcentaje de adiposidad corporal total en el neonato(42).La inclusión de suplementos dietarios en la alimentación materna se ha relacionado en diversos estudios como un factor protector del bajo peso al nacer.…”
unclassified